Neuroprotective effect of Src kinase in hypoxia-ischemia: A systematic review - Christidis, Panagiotis; Vij, Abhya; Petousis, Stamatios; Ghaemmaghami, Javid; Shah, Bhairav V.; Koutroulis, Ioannis; Kratimenos, Panagiotis (Frontiers in Neuroscience, 2022)
Background: Hypoxic-ischemic encephalopathy (HIE) is a major cause of neonatal morbidity and mortality worldwide. While the application of therapeutic hypothermia has improved neurodevelopmental outcomes for some survivors of HIE, this lone treatment option is only available to a subset of affected neonates. Src kinase, an enzyme central to the apoptotic cascade, is a potential pharmacologic target to preserve typical brain development after HIE. Here, we present evidence of the neuroprotective effects of targeting Src kinase in preclinical models of HIE. Methods: We performed a comprehensive literature search using the National Library of Medicine’s MEDLINE database to compile studies examining the impact of Src kinase regulation on neurodevelopment in animal models. Each eligible study was assessed for bias. Results: Twenty studies met the inclusion criteria, and most studies had an intermediate risk for bias. Together, these studies showed that targeting Src kinase resulted in a neuroprotective effect as assessed by neuropathology, enzymatic activity, and neurobehavioral outcomes. Conclusion: Src kinase is an effective neuroprotective target in the setting of acute hypoxic injury. Src kinase inhibition triggers multiple signaling pathways of the sub-membranous focal adhesions and the nucleus, resulting in modulation of calcium signaling and prevention of cell death. Despite the significant heterogeneity of the research studies that we examined, the available evidence can serve as proof of concept for further studies on this promising therapeutic strategy.